Hydrographic shipboard profile data collected within Olympic coast national marine sanctuary, 2005–2023 - Craig M. Risien; Kathryn R. Hough; Jeannette Waddell; Melanie R. Fewings; Brandy T. Cervantes (Data in Brief, 2024)
Olympic Coast National Marine Sanctuary (OCNMS), which was established in 1994 and covers an area of 8257 km2, is located along Washington State's remote and rugged outer coast towards the northernmost extent of the California Current System (CCS). In this region, summertime equatorward winds drive seasonal upwelling of cold, nutrient rich waters onto the continental shelf. These waters help fuel a highly diverse and productive ecosystem that includes marine mammal and seabird communities as well as commercially and culturally important fisheries. The sanctuary is located within the boundaries of the legally defined Usual and Accustomed (U&A) fishing grounds of four Coastal Treaty Tribes, the Hoh Tribe, Makah Tribe, Quileute Tribe, and the Quinault Indian Nation, which hold treaty fishing rights and co-manage fisheries and other natural resources within the sanctuary through state, federal, and international partnerships and agreements. This data article describes shipboard hydrographic Conductivity-Temperature-Depth (CTD) and dissolved oxygen profile data that were collected within the sanctuary at fourteen locations during mooring deployment, recovery, and maintenance cruises between the months of May and October from 2005–2023. The 792 CTD profiles were acquired using Sea-Bird Scientific 19 SeaCAT or 19plus SeaCAT CTD profilers with associated SBE-43 (Sea-Bird Electronics) or Beckman or YSI-type (Yellow Springs Instruments) dissolved oxygen sensors. The data were processed using Sea-Bird Scientific's SBE Data Processing application. These data are needed for improving our understanding of subsurface oceanographic conditions — including marine heat waves, changes in timing of spring transition to upwelling, seasonal hypoxia, and ocean acidification — in this important but undersampled region, and can be used to help improve the management of marine resources regionally and within the sanctuary. The CTD cast data are available via Zenodo at https://doi.org/10.5281/zenodo.10466124.